Designing social learning spaces: evaluating the relationship between perceptions of design quality and student experience in UK higher education - Phan, Thao Nhut Hong (2019)
This research evaluates the relationship between perceptions of design quality and student experience in social learning spaces in the context of UK higher education. Social learning spaces – spaces available for students to gather, such as central buildings, lobbies, cafes and dedicated group-work spaces – are an increasingly important element of university campus planning and estate management. While the contribution that these spaces make toward formal and informal collaborative learning activities has been informed by scholars, little is currently understood about the relationship between the design quality of these spaces and its impact on student engagement; that is, students’ active participation in the academic environment resulting in an enhanced learning experience. A case study employing qualitative and quantitative methods compared two sites; a series of conventional social and group-study spaces in Faculty of Engineering at Nottingham University and the newly designed award-winning social learning space The Pavilion Building at Nottingham Trent University, UK. Findings revealed that student perceptions of design quality have a significant positive correlation with social and learning activities and student experience. The study also identified four key design qualities of social learning spaces: attractiveness, convenience, comfort, and flexibility play a significant role in encouraging positive student experience at different levels, such as student engagement with learning activities as well as social activities, the feeling of support from the university. Furthermore, this research emphasizes the vital role of designers and student views in the process of designing successful social learning spaces.